La ville dans les proto‑fictions climatiques françaises du xixe siècle - Philippe Éthuin (ReS Futurae, 2023)
This article studies climate change and its consequences on cities –the city whose archetype, to a large extent, is Paris – as envisaged by French-speaking authors of 19th century anticipations. It highlights the contemporary resonances regarding the expression of environmental fears within a corpus of texts of anticipation representing the roots of our technoscientific imagination.Firstly, it recalls the context of production of these anticipations in which the questions of the consequences of scientific advances, the domestication of nature and the infinite extension of cities on the environment as seen by fictional texts arise. Then, he discusses the consequences of climate change for urban spaces, the city appearing either as a refuge or as a space doomed to disappear. Finally, it examines the action of humans on the climate by evoking the anthropogenic modifications and the geo‑engineering solutions proposed by several texts of anticipation, most often fanciful.